Stakeholders’ Sapience on the Ease of Use of CBT for Assessment - Omotayo Olabo Obieloden; Amos Ochayi Onojah; Adenike Aderogba Onojah; Kamaldeen Jimoh Muhammed; Ismail Aliu (Economic Education and Entrepreneurship Journal, 2021)
Computer-based Test for assessment is a method of administering test in which the response is electronically assessed and recorded for accuracy. But users’ reaction to the CBT assessment mode differs. This study focused on stakeholders’ Sapience on the ease of use of Computer -Based Examination for assessment as well as the influence of gender on the Ease use of Computer-Based Test for Assessment. The study was a descriptive research of survey type. Random sampling technique was adopted to select 150 stakeholders for the study. Data were analyzed using frequency and percentages and t-test at 0.05 significant level. The findings from the study revealed that stakeholders have high sapience on the ease of use of CBT for assessment. Also, there was no significant difference between male and female stakeholders on the sapience on the ease of use of computer-based test. The study concluded that stakeholders’ sapience on ease of use of the Computer Based Test improved their digital and innovative skills. It was thus recommended among other that lecturer should be trained on the effective use for assessment. Keywords: Stakeholders, Sapience, Gender, Ease of Use, CBT, Assessment